2006
DOI: 10.1111/j.1471-8286.2006.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of microsatellite loci from Olea europaea

Abstract: This study reports 19 simple sequence repeat loci developed from a genomic library of the olive tree ( Olea europaea L.), of which 12 revealed to be polymorphic and informative, ranging from two to 14 alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The majority of SSRs currently identified for olive genotyping carry di-nucleotide repeats (Carriero et al 2002;Cipriani et al 2002;de la Rosa et al 2002;Diaz et al 2006;Rallo et al 2000;Sabino Gil et al 2006;Sefc et al 2000), mostly AG/CT repeats. In order to establish a common set of markers able to produce reliable data for olive cultivar discrimination, Baldoni et al (2009) provided a consensus list of di-nucleotide SSR markers.…”
Section: Communicated By G G Vendraminmentioning
confidence: 99%
“…The majority of SSRs currently identified for olive genotyping carry di-nucleotide repeats (Carriero et al 2002;Cipriani et al 2002;de la Rosa et al 2002;Diaz et al 2006;Rallo et al 2000;Sabino Gil et al 2006;Sefc et al 2000), mostly AG/CT repeats. In order to establish a common set of markers able to produce reliable data for olive cultivar discrimination, Baldoni et al (2009) provided a consensus list of di-nucleotide SSR markers.…”
Section: Communicated By G G Vendraminmentioning
confidence: 99%
“…Microsatellites are highly popular genetic markers because of their codominant inheritance, high abundance, enormous extent of allelic diversity, and the ease of assessing simple sequence repeat (SSR) size variation by PCR with pairs of flanking primers (Agarwal et al, 2008;Muzzalupo et al, 2006Rekik et al, 2008). Recently, many efforts have been made to develop good and reliable molecular tools such as microsatellite markers that could shed light on olive tree genetics (Carriero et al, 2002;Cipriani et al, 2002;De la Rosa et al, 2002;Diaz et al, 2006;Rallo et al, 2000;Sabino Gil et al, 2006;Sefc et al, 2000). They have been used for cultivar identification for elucidating genetic relationships between several olive cultivars (Muzzalupo et al, 2006.…”
mentioning
confidence: 99%
“…Many authors have reported on the development of SSRs in olive and several different sets of markers are actually available for DNA analysis (Sabino Gil et al, 2006).…”
Section: Ssrsmentioning
confidence: 99%